IoT-Enabed Smart Mining:Pengelolaan Air Limbah di Industri Batubara - Impron, Ali; Sutriani , Linda (Universitas Pahlawan Tuanku Tambusai, 2025)
Ensuring wastewater quality in coal mining operations is crucial to comply with environmental regulations. One of the key parameters is the pH level, which must be maintained within the range of 6-9. Currently, the monitoring process is manual, involving the use of litmus paper and visual comparison to estimate the pH level. The adjustment of pH is achieved by manually adding limestone until the desired range is met. This research proposes an automated solution leveraging Internet of Things (IoT) technology to streamline both monitoring and control processes. By integrating pH sensors into the water system and employing IoT-enabled relay controls for limestone dispensing, the system enables real-time pH monitoring and automatic limestone release. The proposed system aims to improve the efficiency and accuracy of wastewater treatment processes, aligning with the digitalization efforts and Industry 4.0 standards.